2008
DOI: 10.1016/j.paid.2007.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Exploring emotion-regulation and autonomic physiology in metastatic breast cancer patients: Repression, suppression, and restraint of hostility

Abstract: We examined relationships between three emotion-regulation constructs and autonomic physiology in metastatic breast cancer patients (N = 31). Autonomic measures are not often studied in breast cancer patients and may provide evidence of an increase in allostatic load. Patients included participated as part of a larger clinical trial of supportive-expressive group therapy. Systolic and diastolic blood pressure and heart rate were assessed at a semi-annual follow-up. We averaged 3 resting assessments and used me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 59 publications
2
23
0
Order By: Relevance
“…psychophysiological variables (see Giese-Davis, Conrad, Nouriani, & Spiegel, 2008) to extend the findings. Because of the cross-sectional design, we cannot rule out alternative explanations for the findings, e.g., that differences between the groups may be the consequence of past depression in the sense of a scar effect or may even be due to symptom contamination as recovered depressed participants have experienced more intense emotion in the past than controls.…”
Section: Discussionmentioning
confidence: 57%
“…psychophysiological variables (see Giese-Davis, Conrad, Nouriani, & Spiegel, 2008) to extend the findings. Because of the cross-sectional design, we cannot rule out alternative explanations for the findings, e.g., that differences between the groups may be the consequence of past depression in the sense of a scar effect or may even be due to symptom contamination as recovered depressed participants have experienced more intense emotion in the past than controls.…”
Section: Discussionmentioning
confidence: 57%
“…However, other studies found that emotion suppression or dampening (as measured by the CECS) was not significantly related to psychological distress, autonomic physiology, or survival Giese-Davis et al, 2008;Goodwin et al, 2004;Nakatani et al, 2014;Watson et al, 1999).Emotional dampening, as measured by the WCQ, was associated with longer survival times (Andreu et al, 2012;Classen et al, 1996;Reynolds et al, 2000;Schlatter et al, 2010;Tamagawa et al, 2013).…”
Section: Dimensions Of Emotional Regulation Found In the Included Stumentioning
confidence: 96%
“…One study comparing repressive versus nonrepressive cancer patients showed that repressors reported less severe chemotherapy‐induced side effects and less information exchange regarding their cancer with significant others (Ward, Leventhal, & Love, ), an example of a characterological repressive coping pattern. Despite few self‐reported health problems, repressors often exhibit aberrant autonomic physiology (Giese‐Davis, Conrad, Nouriani, & Spiegel, ) and diurnal cortisol secretion consistent with a stress response (Giese‐Davis, Sephton, Abercrombie, Duran, & Spiegel, ; Giese‐Davis, DiMiceli, Sephton, & Spiegel, ). These same physiological patterns have also been associated with early mortality in metastatic breast cancer patients (Sephton, Sapolsky, Kraemer, & Spiegel, ).…”
Section: Mindfulness and Healthmentioning
confidence: 99%